Integrating SERVQUAL and SWOT methods to design strategies for enhancing the quality of property consulting services - Surya, Josephine; Abidin, Abidin (Journal Industrial Servicess, 2023)
Jabodetabek, as the hub of national economic growth in Indonesia, has emerged as a countermagnet for capital city development. This has sparked heightened competition among property agents striving to boost their property sales. PT Rajawali Sumber Berkat Abadi operates in the property industry, focusing on property consulting services. In this fiercely competitive landscape, the company aims to elevate its service quality. To achieve this, they plan to devise a strategy using the Servqual and SWOT methods. The Servqual questionnaire will help identify specific service deficiencies and strengths in property consulting. Additionally, it will calculate comparative values to gauge their significance. Alongside, a SWOT analysis will pinpoint weaknesses, strengths, opportunities, and threats. This will involve discussions with the company's commissioners and calculations using AHP and QSPM methods. The analysis revealed three primary service deficiencies, despite an overall good quality score. It was found that the optimal strategy design lies in the Strength-Opportunity (S-O) strategy. This approach translates into several work programs aimed at bolstering market penetration. Four S-O strategies were outlined, consisting of 20 distinct work programs. Furthermore, a QSPM matrix calculation was employed to reinforce the SWOT matrix’s findings. This aimed to pinpoint the most pertinent company strategy for implementation. The strategy design obtained a Total Attractiveness Score (TAS) of 9.24, affirming its viability.